A multi-class multi-residue method for the analysis of polyether ionophores, tetracyclines and sulfonamides in multi-matrices of animal and aquaculture fish tissues by ultra-high performance liquid chromatography tandem mass spectrometry. Issue 3 (3rd March 2020) - Abafe, Ovokeroye A.; Gatyeni, Pumza; Matika, Lungile
ABSTRACT: An ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS) based multiclass multi-residue method for the simultaneous analysis of 5 polyether ionophores, 4 tetracycline and 10 sulfonamides in animal and aquaculture fish tissues was developed and validated. Sample extraction and clean-up were based on a modified QuEChERS method. The method was validated using an in-house validation based on performance characteristics modified from Commission Decision 2002/657/EC. Both matrix effect and uncertainties associated with sample preparation and instrumental analysis were minimised by the use of matrix-matched calibrations. Recoveries of analytes were generally satisfactory and typically fell between 80% and 113%. The repeatability and intermediate reproducibility measured as relative standard deviations were in most cases less than 15% (n = 63). The decision limit (CCα) and detection capability (CCβ) ranged from 110.7 to 125.8 and 121.5 to 151.7 µg kg −1 for tetracyclines, 113.4 to 118.3 and 116.8 to 126.5 µg kg −1 for sulfonamides and 50.8 to 52.4 and 51.5 to 55.6 µg kg −1 for polyether ionophores, respectively. The method displayed its fitness for purpose through satisfactory results obtained in international proficiency testing schemes. The method was applied to animal and aquaculture fish tissues obtained from different sources in South Africa. Polyether ionophores were predominantly detected in samples in the range 4.26–290.10 µg/kg. Oxytetracycline was found in one porcine liver sample; however, none of the targeted analytes were present above the detection limit in the aquaculture samples. Graphical Abstract: